Cryogenic Engineering Fifty Years of Progress - Timmerhaus, Klaus D.; Reed, Richard P.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2007)
Cryogenic Engineering: Fifty Years of Progress is a benchmark reference work which chronicles the major developments in the field. Starting with an historical background dating to the 1850s, this book reviews the development of data resources now available for cryogenic fields and properties of materials. The advances in cryogenic fundamentals are covered by reviews of cryogenic principles, cryogenic insulation, low-loss storage systems, modern liquefaction processes, helium cryogenics and low-temperature thermometry. Several well-established applications resulting from cryogenic advances include aerospace cryocoolers and refrigerators, use of LTS and HTS systems in electrical applications, and recent changes in cryopreservation. Extensive references are provided for the readers interested in the details of these cryogenic engineering advances.
Background Information -- Historical Summary of Cryogenic Activity Prior to 1950 -- Advances in Cryogenic Data Development over the Past 50 Years -- Sources of Cryogenic Data and Information -- Trends and Advances in Cryogenic Materials -- History and Applications of Nonmetallic Materials -- Improvement in Cryogenic Fundamentals over the Past 50 Years -- Advances in Cryogenic Principles -- Insulation Progress since the Mid-1950s -- Development of Low-Loss Storage of Cryogenic Liquids over the Past 50 Years -- Fifty-Years’ Development of Cryogenic Liquefaction Processes -- Advances in Helium Cryogenics -- Lessons Learned in 50 Years of Cryogenic Thermometry -- Cryogenic Applications Development Over the Past 50 Years -- Aerospace Coolers: A 50-Year Quest for Long-Life Cryogenic Cooling in Space -- Understanding Properties and Fabrication Processes of Superconducting Nb3Sn Wires -- High-Temperature Superconductors: A Review of YBa2Cu3O6+x and (Bi,Pb)2Sr2Ca2Cu3O10 -- A Paradigm Shift in Cryopreservation: Molecular-Based Advances to Improve Outcome.
Keywords: Thermodynamics; Superconductivity; Superconductors; Heat engineering; Heat transfer; Mass transfer; Space sciences; Fluids; Fluid mechanics; Thermodynamics; Strongly Correlated Systems, Superconductivity; Engineering Thermodynamics, Heat and Mass Transfer; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Fluid- and Aerodynamics; Engineering Fluid Dynamics